ASSESSING HYDRO-OCEANOGRAPHY CONDITIONS USING DELFT3D NUMERICAL MODEL FOR LAMPIA PORT, BONE GULF, INDONESIA - Bayu Wintoro; Munawir Bintang Pratama; Alvin Yesaya; Amirah Zakiyyah (Universitas Udayana, 2025)
Lampia Port is part of the Coastal Area located in The Bone Gulf, Central Sulawesi, and serves as one of the docking ports for passenger and cargo loading and unloading activities in Central Sulawesi. This study was conducted to identify the tidal, current, and erosion/sedimentation characteristics in the coastal waters around the port as parameters for planning the rehabilitation and development of the port. Tidal, current, and erosion/sedimentation analyses were performed using numerical modeling on the Delft3D-FLOW and Delft3D-WAVE modules of the Delft3D software developed by Deltares. The data used in the modeling include bathymetry and local tidal elevations obtained from field surveys. The modeling was carried out using the nesting method with three levels of grid resolution, with the highest resolution at 43 x 43 m² approaching the Coastal Waters of Lampia Port. The modeling results were validated with field data in the form of tidal elevations at two points in the coastal area around the study location. The modeling results indicate that the tidal range in the Lampia Coastal Waters reaches 3,54 meters with a mixed – semi-diurnal type. The modeling results also show the current patterns in the Lampia Coastal Waters with estimated magnitudes ranging from 0.5 m/s to 1 m/s. Additionally, erosion/sedimentation patterns around Lampia Port range between 3-10 cm per year.